2005
DOI: 10.1016/s1472-6483(10)61662-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the occurrence of the empty follicle syndrome a predictor that a subsequent stimulated cycle will be an unfavourable one?

Abstract: Several hypotheses have been advanced to explain empty follicle syndrome (EFS) but it remains a controversial topic. This paper reports experience with three IVF cycles in which no oocytes were collected. In all cases, an additional IVF cycle was performed. The ovarian stimulation protocol, ultrasound and hormonal surveillance methods, human chorionic gonadotrophin timing and oocyte retrieval technique were similar in all patients. The assessment of additional cycles demonstrated a poor response in terms of oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…2 It has been proposed that GEFS is caused by dysfunctional folliculogenesis, ovarian aging, or genetic factors including pericentric inversion of chromosome 2 and LHCGR (MIM: 152790) mutations. [3][4][5][6][7] A retrospective study of 12,359 individuals who underwent assisted reproductive technology (ART) revealed that the prevalence of GEFS was about 0.016%. 8 Without oocytes for fertilization, these individuals fail to achieve pregnancy after a demanding and expensive medical intervention, resulting in stress to both physicians and the individuals themselves.…”
Section: Efs Can Be Classified As Either False Efs (Fefs) or Genuine mentioning
confidence: 99%
“…2 It has been proposed that GEFS is caused by dysfunctional folliculogenesis, ovarian aging, or genetic factors including pericentric inversion of chromosome 2 and LHCGR (MIM: 152790) mutations. [3][4][5][6][7] A retrospective study of 12,359 individuals who underwent assisted reproductive technology (ART) revealed that the prevalence of GEFS was about 0.016%. 8 Without oocytes for fertilization, these individuals fail to achieve pregnancy after a demanding and expensive medical intervention, resulting in stress to both physicians and the individuals themselves.…”
Section: Efs Can Be Classified As Either False Efs (Fefs) or Genuine mentioning
confidence: 99%
“…Several reports suggest that a significant part of genuine EFS is associated with ovarian ageing [4,8,20-22]. Ovarian ageing is characterized by poorly functioning GC [23].…”
Section: Underlying Mechanismmentioning
confidence: 99%
“…On the other hand, some suggest the occurrence of EFS would indicate a poor outcome in subsequent cycles. Lorusso et al [20] reported in their case series that poor quality oocytes were obtained after an EFS cycle and suggested that the empty cycle could be a predictor that a subsequent stimulated cycle will be an unfavorable one. Later, Coskun et al [9] also reported poor outcomes after genuine EFS.…”
Section: Prognosismentioning
confidence: 99%
“…A number of investigators have related failure to obtain oocytes to ovarian ageing (Ben-Shlomo et al, 1991;Lorusso et al, 2005). This is characterized by the following: poorly functional granulosa cells and oocytes unable to achieve maturity (Ben-Shlomo et al, 1991); underlying ovarian dysfunction resulting in impaired follicular maturation or ovulation (Bustillo, 2004); an error in folliculogenesis or premature apoptosis of the oocytes that still continued follicular growth (Desai et al, 2009); strong attachment of cumulus cell complexes to the follicular wall; dysfunctional ovulation induction (Khalaf et al, 2000); a borderline form of poor response to ovarian stimulation (Lorusso et al, 2005); or a genetic defect (Yariz et al, 2011). In our opinion, the different ostradiol-follicle ratios found could reflect poor oocyte quality.…”
Section: P-valuementioning
confidence: 99%